The digital mental health revolution: Transforming care through innovation and scale-up - Roland,J; Lawrance,E; Insel,T; Christensen,H (The World Innovation Summit for Health (WISH), 2020)
The report reviews how to prepare and navigate innovations and their potential to address critical health needs.